2013
DOI: 10.11621/pir.2013.0405
|View full text |Cite
|
Sign up to set email alerts
|

Moral emotions, conscience, and cognitive dissonance

Abstract: One of the central topics in the studies of O. K. Tikhomirov and his collaborators was the link between cognitive and emotional processes. It is important not only how emotions are involved in the process of the productive performance of thinking tasks but also how cognitive processes mediate the involvement of the emotions in the regulation of activity. The efficacy of this regulation is represented through goal achievement and also through the correction of one's actions in the case of wrongdoing. Reformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The Madurese as migrants inhabited the lands of the Dayaknese and enjoyed the available resources and business opportunities there. This is in line with the assumption of the cognitive dissonance theory (Breslavs, 2013;Festinger, 1962), where people reduce feelings of dissonance by changing their cognition. The students in the study already knew that the conflicts between Dayaknese and Madurese had been widely published in media, and that the conflicts had been ongoing.…”
Section: Javanese Ratings Towards the Madurese Photossupporting
confidence: 85%
See 1 more Smart Citation
“…The Madurese as migrants inhabited the lands of the Dayaknese and enjoyed the available resources and business opportunities there. This is in line with the assumption of the cognitive dissonance theory (Breslavs, 2013;Festinger, 1962), where people reduce feelings of dissonance by changing their cognition. The students in the study already knew that the conflicts between Dayaknese and Madurese had been widely published in media, and that the conflicts had been ongoing.…”
Section: Javanese Ratings Towards the Madurese Photossupporting
confidence: 85%
“…In order to reduce this guilt, it was predicted that the younger generation of Madurese would compensate for their guilt by perceiving Dayaknese people in a more positive way. This corresponds with cognitive dissonance theory (Breslavs, 2013;Festinger, 1962), where people reduce the feeling of dissonance by changing their cognition. To the best of our knowledge, there has been no study to test this argument in the context of intergroup conflict.…”
Section: Madurese Versus Dayaknese Conflictmentioning
confidence: 70%
“…Incorporating an interview in future studies may add a richer dataset to the self-report measures and accords better insight into the youths' moral emotions. Sometimes the reliance on self-reports alone may represent the desired rather than the real experience and feeling (Breslavs, 2013).…”
Section: Limitation and Study Forwardmentioning
confidence: 99%
“…Troubled conscience has often been described as being connected with feelings of shame and guilt. Shame is related to a real or imaged audience and is focused on self‐image, while guilt is focused on the victim of the transgression . It was evident that the interviewees were very concerned about the older people to whom they had not provided good care in the way that they described how they kept their conscience out of trouble.…”
Section: Comprehensive Interpretation and Reflectionsmentioning
confidence: 99%
“…Having a strong conscience has been reported as one of the components of clinical competency in one Iranian study , and people who have the personality trait of conscientiousness have been found to have higher levels of job satisfaction and lower levels of job stress . Guilt is found to promote reparative and pro‐social behaviour . The interviewees described that they tried to compensate by providing better care to the older people when they felt they had failed.…”
Section: Comprehensive Interpretation and Reflectionsmentioning
confidence: 99%